1999
DOI: 10.1046/j.1524-4725.1999.99005.x
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative and Postoperative Topical Tretinoin on High-Tension Excisional Wounds and Full-Thickness Skin Grafts in a Porcine Model: A Pilot Study

Abstract: The collagen-inducing effects of topical tretinoin do not appear to enhance the healing of high-tension excisional surgery wounds in a porcine model. Tretinoin does not appear to improve the survival of full-thickness skin grafts and, in fact, a detrimental effect was apparent in our model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Several past studies have, in fact, demonstrated beneficial effects of retinoid use in wound healing. Although most of these studies have focused on wounds in the skin, [11][12][13][14][15][16][17] retinoid efficacy has also been demonstrated in healing of wounds in other tissues-bone, cornea, respiratory tract, upper digestive system, and gut. [18][19][20][21][22][23][24][25] Although retinoids have beneficial activities, skin irritation is commonly seen following topical application of RA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several past studies have, in fact, demonstrated beneficial effects of retinoid use in wound healing. Although most of these studies have focused on wounds in the skin, [11][12][13][14][15][16][17] retinoid efficacy has also been demonstrated in healing of wounds in other tissues-bone, cornea, respiratory tract, upper digestive system, and gut. [18][19][20][21][22][23][24][25] Although retinoids have beneficial activities, skin irritation is commonly seen following topical application of RA.…”
Section: Discussionmentioning
confidence: 99%
“…Although most studies have focused on wounds in the skin, [11][12][13][14][15][16][17] retinoid efficacy has also been demonstrated in healing of wounds in other tissues (bone, cornea, respiratory tract, upper digestive system, and gut). 27 Likewise, skin irritation is also a complication with synthetic retinoidal agents currently on the market.…”
Section: Introductionmentioning
confidence: 99%
“…4 Application on already open wounds, however, has yielded varying results. In some animal models, tretinoin therapy has been found to enhance healing 4,15,16 ; in others, it has been shown to have no effect 17 or to cause inflammation and excessive granulation without reepithelialization. 5,18 It has been suggested that tretinoin may be too irritating when applied after wounding has occurred, especially to the surrounding skin.…”
Section: Commentmentioning
confidence: 99%
“…Use of direct-current electrical field, hyperbaric oxygen therapy, and pharmacologic applications of phenytoin, tretinoin, and fibrin tissue adhesive glue have been reported. [3][4][5][6][7][8][9][10] Growth factors are members of a large functional group of polypeptide regulatory molecules, secreted by many different cell lines through autocrine and paracrine fashions, influencing the biologic activities of responsive cells. 14,15 Experimental studies have found that the levels of growth factors increased at the wound sites, which promoted nutrient flow, angiogenesis, and vascular remodeling necessary for skin graft survival.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, some efforts have been made to improve skin graft take in such wounds, including use of direct-current electrical field, hyperbaric oxygen therapy, and pharmacologic applications of phenytoin, tretinoin, and fibrin tissue adhesive glue. [3][4][5][6][7][8][9][10] The results from these methods were inconsistent.…”
mentioning
confidence: 99%